Respuesta :
If you use the polynomial remainder theorem, right away you get a remainder of
[tex]h(-3)=(-3)^4+(-3)^2-2=88[/tex]
Answer: The remainder would be 88.
Step-by-step explanation:
Since we have given that
[tex]f(h)=h^4+h^2-2[/tex]
and
[tex]g(h)=h+3[/tex]
We need to find the remainder while dividing f(h) by g(h).
First we take, g(h) = 0
[tex]h+3=0\\\\h=-3[/tex]
Now, we put the value of h = -3 in f(h) to get the remainder.
[tex]f(-3)=(-3)^4+(-3)^2-2\\\\f(-3)=81+9-2\\\\f(-3)=90-2\\\\f(h)=88[/tex]
Hence, the remainder would be 88.